ABO and Rh-D blood group distribution in a rural population of Bangladesh - Hira, RM; Dhali, LK; Dhali, ND; Akash, DK (Mediscope, 2015)
This is an observational cross-sectional study aiming to identify the distribution patterns of ABO and Rh-D blood group in a rural population of Bagerhat District, Bangladesh in order to promote social awareness and safe blood transfusion among the population. After proper ethical consideration, a total of 164 people of a village in Bagerhat District were included in this study. They were selected irrespective of age and sex by systematic random sampling. ABO and Rh-D blood groups were determined by the antigen antibody agglutination test of slide method. The ABO group distribution, O (34.1%), A (26.2%), B (25.6% and AB (14.0%). Of the respondents, 105 (64.0%) were male and 59 (36.0%). The frequency of group O+ve comprised the highest (32.9%) of the samples followed by group A+ve, B+ve and AB+ve. The majority of the subjects were Rh-D positive (94.5%). It is observed that Rh-D positive group is more common in subjects with O group whereas Rh-D negative group is more common in B group. Most common blood group among this village population was O+ve which can safely be transfused to any other group. The study of blood grouping can generate database and create social awareness about self-blood grouping and safe blood transfusion among the population. Mediscope Vol. 2, No. 1: 2015, Pages 22-26